Dispersity of milk fat under the influence of iodidecontaining supplements in the goat ration - Рижкова, Т. М.; Васильєв, В. С.; Гончарова, І. І.; Лівощенко, І. М. (Scientific Progress & Innovations, 2012)
The results of influence of hydrous creep-feeding on the technological peculiarities of goat milk and in particular on the dispersity of fat globules have been shown in this article. During milk testing of goats, which had some additional creep-feeding such as «Elamin» and potassium-iodine in their ration it has been determined that a fat component has higher dispersity of fat globules thatincreases milk assimilability by human being. Goat milk which contains iodine components is more technological than goat milk without these components becanse its not needed to conduct homogenization.